Properties of Pineapple Leaf Fiber (PALF) Reinforced Polypropylene (PP) composites - Nurjannah, Salim; Fatin Nursyafiqah, Johari; Rasidi, Roslan; Nurul Huda, Abu Bakar; Nurlin, Abu Samah; Siti Maznah, Kabeb; Siti Noorbaini, Sarmin (John Wiley and Sons Inc, 2025)
Pineapple leaf fiber (PALF) is an abundant natural fiber that is produced from agricultural plantations in Malaysia. Typically, after three times the pineapple yield, pineapple leaf waste is burned, which can cause an environmental issue. PALF has the potential to be converted into fiber-reinforced composites. PALF surpasses other natural fibers in terms of mechanical characteristics due to its high specific strength. Therefore, this study aims to investigate the effects of different PALF fiber loadings on PALF/polypropylene (PP) composite properties. The sample of composites is fabricated with three different PALF fiber loadings (0 wt%, 5 wt%, and 10 wt%). The fabrication is made using an extruder and injection molding techniques. The PALF/PP composite properties are then investigated based on thermal, mechanical, water absorption, and morphological properties. The results found that PALF/PP composites are high in thermal resistance. A comparison of the experimental values for the tensile strength shows that the tensile strength increases with the increase in PALF loading. The study also found that PP, PP/PALF 5%wt, and PP/PALF 10%wt composites absorbed less water. Overall, the prepared PALF/PP composites can withstand high temperatures and have high mechanical strength. The composites also exhibit low water absorption, which is a good criterion for paneling products such as furniture and decorative panels.